Demo: MobiUS: A Together-Viewing Mobile Video Experience - Shen, Jacky; Li, Yanlin; Peng, Chunyi; Zhang, Yongguang (MobiSys'07 Demo Session, 2007)
This demo, MobiUS, shows a specific together-viewing mobile video application in which a higher (doubled) resolution video is played back across screens of two mobile devices placed side by side, which is a case study of the envisioned new better-together mobile application paradigm where multiple mobile devices are placed in a close proximity.